Hearing things: Inside outness and ‘sonic ghosts’ - Grant, Jane (Technoetic arts : a journal of speculative research, 2012)
This article will consider sound as a glue between internal and external experience, a link between sensing and cognition, memory and perception. In looking at research in neuroscience, specifically Eugene Izhikevich’s work with models of spiking neurons, parallels may be drawn with faulty source monitoring where a subject cannot differentiate between external and internal stimuli, and with a collapsing of present into the past. These ideas will be discussed through a number of sonic artworks that have neural plasticity, space and location at their core.